A comparative study regarding the intraoperative efficacy of conventional open (Milligan-Morgan) and harmonic scalpel haemorrhoidectomies - Madankar, Swapnil P.; Jatkar, Girish L.; Dandge, Mahendra S. (International Surgery Journal, 2019)
Background: Human beings have suffered from haemorrhoids since they have started to walk. The surgical treatment for haemorrhoids is called ‘Haemorrhoidectomy’. Many techniques have been developed to minimize the morbidity and hasten the recovery. This study compares two such techniques: conventional open haemorrhoidectomy (Milligan-Morgan) and the harmonic scalpel haemorrhoidectomy, in terms of intraoperative efficacy. Methods: This was a randomized, prospective, single blind (patients), non-crossover type interventional study was carried out on patients more than 18 years of age presenting with haemorrhoids requiring surgical treatment. They were randomly divided into two groups and the surgeries were carried out accordingly. Intraoperative and immediate post-operative monitoring was done. Results: Operative time, intraoperative and immediate post-operative blood loss was less in the harmonic group compared to the conventional group. Conclusions: Harmonic scalpel haemorrhoidectomy is better surgical technique than conventional open haemorrhoidectomy as it has better intraoperative efficacy having significant positive impact on the morbidity and recovery of the patient.